The miR-30-5p/TIA-1 axis directs cellular senescence by regulating mitochondrial dynamics - Tak, Hyosun; Cha, Seongho; Hong, Youlim; Jung, Myeongwoo; Ryu, Seungyeon; Han, Sukyoung; Jeong, Seung Min; Kim, Wook; Lee, Eun Kyung (Cell Death and Disease, 2024)
Senescent cells exhibit a diverse spectrum of changes in their morphology, proliferative capacity, senescence-associated secretory phenotype (SASP) production, and mitochondrial homeostasis. These cells often manifest with elongated mitochondria, a hallmark of cellular senescence. However, the precise regulatory mechanisms orchestrating this phenomenon remain predominantly unexplored. In this study, we provide compelling evidence for decreases in TIA-1, a pivotal regulator of mitochondrial dynamics, in models of both replicative senescence and ionizing radiation (IR)-induced senescence. The downregulation of TIA-1 was determined to trigger mitochondrial elongation and enhance the expression of senescence-associated β-galactosidase, a marker of cellular senescence, in human foreskin fibroblast HS27 cells and human keratinocyte HaCaT cells. Conversely, the overexpression of TIA-1 mitigated IR-induced cellular senescence. Notably, we identified the miR-30-5p family as a novel factor regulating TIA-1 expression. Augmented expression of the miR-30-5p family was responsible for driving mitochondrial elongation and promoting cellular senescence in response to IR. Taken together, our findings underscore the significance of the miR-30-5p/TIA-1 axis in governing mitochondrial dynamics and cellular senescence.
Keywords: Cell Line; Cellular Senescence; Fibroblasts; Humans; Keratinocytes; MicroRNAs; Mitochondria; Mitochondrial Dynamics; Radiation, Ionizing; Signal Transduction; T-Cell Intracellular Antigen-1